The Effect of Brand Image, Brand Experience and Brand Loyalty towards Purchase Intention On Apple Smartphone in Makassar - William Sanjaya; Muhammad Asdar; Abdul Razak Munir (Hasanuddin Journal of Business Strategy, 2020)
This research aims to analyze the effect of brand image, brand experience, and brand loyalty towards purchase intention on Apple smartphones in Makassar. The method used in this research is a quantitative method using multiple regression. The population in this research was Apple Smartphone users in Makassar; the sample in this research was 100 people. Data collected using questionnaires. This study uses multiple regression analysis statistical tools; the hypothesis tested using the F test (simultaneous) and t-test (partial). The results of this research showed that brand image has a positive and significant effect on purchase intention, brand experience has a positive and significant effect on purchase intention, brand loyalty has a positive and significant effect on purchase intention. Brand image, brand experience, and brand loyalty simultaneously have a positive and significant effect on purchase intention.